Down Regulation of the Expression of ELMO3 by COX2 Inhibitor Suppresses Tumor Growth and Metastasis in Non-Small-Cell Lung Cancer - Pan, Cailong; Zhang, Yong; Meng, Qinghai; Dai, Guoliang; Jiang, Zhitao; Bao, Hongguang (Frontiers in Oncology, 2019)
Non-small cell lung cancer (NSCLC) is one of the most common malignancies. Studies have shown that engulfment and cell motility 3 (ELMO3) is highly expressed in NSCLC and can be used as a novel biomarker, but its underlying mechanism remains to be explored. The aim of this study was to investigate the mechanism by which ELMO3 may be down-regulated by COX-2 inhibitors to inhibit NSCLC. NSCLC tissue and adjacent normal lung tissue from 24 patients were used to detect the mRNA and protein expression of ELMO3, COX-2 and other related proteins by Western blot, RT-PCR, and Immunohistochemical analysis. Lewis Lung carcinoma (LLC) cells were used to investigate the effects and the mechanism of siELMO3 and COX-2 inhibitor. C57BL/6 mice inoculated with LLC cells by subcutaneous (s.c.) injection were used to detect the in vivo effects of cox-2 inhibitor. The expression of ELMO3 and cyclooxygenase-2 (COX-2) in human NSCLC tissues was significantly increased compared with that in the adjacent normal tissues. ELMO3 exhibited a positive correlation with COX-2 expression. Moreover, knockdown of ELMO3 suppressed the epithelial-mesenchymal transition (EMT), adhesion, and metastasis of Lewis lung carcinoma (LLC) cells. Importantly, Parecoxib, a selective inhibitor of COX-2, significantly reduced the expression of ELMO3 and EMT in LLC cells and LLC-bearing mice. Furthermore, it could inhibit the growth, adhesion and metastasis of LLC cells in vitro. Our results demonstrate that down regulation of ELMO3 suppressed growth and metastasis of lung cancer by inhibiting EMT. Parecoxib could reduce ELMO3 expression and suppress growth and metastasis of lung cancer, which might be a useful chemotherapeutic agent for inhibiting metastasis and recurrence of NSCLC.